2018
DOI: 10.18203/2320-1770.ijrcog20184961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug resistance (MDR) and extended spectrum beta-lactamases (ESBLs) among uropathogenic Escherichia coli isolates from female patients in a tertiary care hospital in North India

Abstract: Background: Urinary tract infection (UTI) is a common bacterial infection in women. It is very common during pregnancy and may present as asymptomatic bacteriuria. Escherichia coli is the primary urinary pathogen accounting for 74-90% of uncomplicated urinary tract infection. The aim of the study was to evaluate in-vitro antibiotic susceptibility among urine isolates of Escherichia coli and prevalence of resistance marker like ESBL producer and MDR status.Methods: Mid-stream urine samples of 205 female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…11,16 Resistance to nitrofurantoin in most studies was in the range of 10-20%. 11,14,18,19 In our study and Ranjini CY et al 3 nitrofurantoin resistance was seen in 28.42% and 26.77% isolates respectively while Gupta V et al 16 found no resistance. The ICMR, antimicrobial resistance surveillance network, 2018 data has reported 88.1% and 86.0% of the isolates to be sensitive to two old antibiotics, fosfomycin and nitrofurantoin respectively.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…11,16 Resistance to nitrofurantoin in most studies was in the range of 10-20%. 11,14,18,19 In our study and Ranjini CY et al 3 nitrofurantoin resistance was seen in 28.42% and 26.77% isolates respectively while Gupta V et al 16 found no resistance. The ICMR, antimicrobial resistance surveillance network, 2018 data has reported 88.1% and 86.0% of the isolates to be sensitive to two old antibiotics, fosfomycin and nitrofurantoin respectively.…”
Section: Discussionsupporting
confidence: 52%
“…Among β-lactamase producers fosfomycin resistance was lowest (7.37%). Low resistance to fosfomycin has also been observed by Das B et al (7.7%) 14 and Rahman MS et al (4.0%). 2 In few studies all the β-lactamase producing isolates were found to be susceptible to fosfomycin.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations